At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Answer:
(3, 6 )
Step-by-step explanation:
Given the 2 equations
y = 5x - 9 → (1)
y = x + 3 → (2)
Substitute y = 5x - 9 into (2)
5x - 9 = x + 3 ( subtract x from both sides )
4x - 9 = 3 ( add 9 to both sides )
4x = 12 ( divide both sides by 4 )
x = 3
Substitute x = 3 into either of the 2 equations and evaluate for y
Substituting into (2)
y = 3 + 3 = 6
solution is (3, 6 )
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.